Analisis Kemampuan Reversibilitas Siswa MTs Patra Mandiri Kelas VIII Pada Pembelajaran Geometri - Sulastri, Irma; Marlina, Leni; Muslimahayati, Muslimahayati (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2019)
This study aims to determine the reversibility ability of class VIII students in learning geometry. This ability is known after all students complete the five questions given and some students are selected to be interviewed. The test instrument in the form of five questions of reversibility ability has been validated and is worth testing. The research subjects were 38 class VIII E MTs Patra Mandiri Palembang students in the 2018/2019 academic year. The type of research used in this study is descriptive qualitative research. The data are concluded and documentation analyzed using the miliage model and huberman qualitative data analysis techniques, namely data reduction data display and conclusion drawing. From the result of the research conducted, it was shown that the student reversibility ability in geometry learning, namely (1) students who possessed high reversibility ability could meet the reciprocity indicator (2) students who have the ability to meet some indicators of reversibility ability (3) students with low ability do not meet the predictability of reversibility abilities.